Reading in the classroom: how do English as an additional language teachers see it? - Moro, Beatriz Ilibio; Rossa, Adriana Argelim (BELT - Brazilian English Language Teaching Journal, 2011)
Several studies on reading in additional language classrooms are based on the description of cognitive processes, in the creation of new material for additional language learning and / or in its goals. However, these studies do not address the view that additional language teachers, especially Brazilian teachers of English, have of the processes and of their role as helpers, guiders of the act of reading. Therefore, through this research we aim to provide an overview of the teachers’ vision of the importance of reading and its important role, in an attempt to generate a self-assessment by the teachers, besides showing what has been done in practice, encouraging a further strengthening of academic research and classroom.